Evaluation of Performance of Rajasri Birds under Different Management Situations - Preetam, V. Chinni; Gurram, Srinivas; Qudratullah, S. (Indian Journal of Animal Nutrition, 2019)
A study was conducted to evaluate the performance and physical & chemical composition of crop contents of Rajasri bird reared under different systems. The control group was reared under intensive system offering ad lib. feed, while second and third groups were maintained under semi intensive system providing 20 and 40 percent of ad lib. feed respectively. The remaining two treatment groups were reared under scavenging, one group at farm (SC-F) and the other at farmerâ€™s backyard (SC). Significantly (P<0.05) higher body weight was noticed in control group compared to other groups at 40 and 60 weeks of age. The mean hen day production was significantly (P<0.05) better with control group and least with 20% and 40% ad lib. groups. On physical verification it was observed that 35.88 & 52.02% grains, 15.06 & 15.39% greens, 24.26 and 6.33% kitchen wastes, 1.44 and 3.84% animal protein sources and 23.36 & 22.41% of other items at 20 and 60 weeks of age respectively. The chemical composition revealed that the dry matter of the crop contents recorded as 36.34 & 36.04% at 20 and 60 weeks of age respectively.Â The nutrients like crude protein, ether extract, total ash, crude fibre and nitrogen free extract were recorded as of 9.68 & 10.59, 6.53 & 3.57, 31.18 & 23.80, 18.05 & 28.67 and 34.58 & 33.38 percent on dry matter basis at 20 and 60 weeks of age respectively.